ccTLD best practices for the prevention and resolution of intellectual property disputes (WIPO GenevaCH, 2001)
Presents a set of voluntary guidelines for the development of practices and policies to curb abusive and bad faith registrations of protected names, and to resolve disputes.
Keywords: INTELLECTUAL PROPERTY